Custody protection between the prejudice of the legislative text and the jurisprudence of the family affairs judge - Bousbiat, Saoussen (Journal of Human Sciences, 2020)
The interests of the parents often come into conflict after the dissolution of the conjugal bond, according to which it is decided that the children will stay with one or the other who is legally entitled to custody, and since the child being cared for does not know his interest, the legislator has granted to a third party outside the relationship the power to value this interest, which is the judge.In the absence of a legal text defining the meaning of the interest of the child in care, the family affairs judge found an open field to express it to guarantee the psychological, emotional and social stability of the child in care.However, the exercise of the judge's discretion was not sufficient to protect the interest of custody child in the light of the legal vacuum to which certain questions such as the visit rights.